ANALISIS PENERAPAN PROJECT-BASED LEARNING (PJBL) TERINTEGRASI STEM DALAM MENINGKATKAN KETERAMPILAN ABAD KE-21 PADA PEMBELAJARAN IPA: SYSTEMATIC LITERATURE REVIEW - Febry Yeni Gultom; Odor Debora Pita Uli Sinaga; Irma Ria Vael Nasution (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of STEM-integrated Project-Based Learning (PjBL) in enhancing 21st century skills in science education through a Systematic Literature Review (SLR) approach. This study reviewed 17 scientific articles published between 2020 and 2024, obtained from the Google Scholar database. The analysis process was conducted through identification, screening, and selection stages based on inclusion and exclusion criteria. The results indicate that the implementation of STEM-integrated PjBL consistently has a positive impact on 21st century skills, particularly critical thinking, creativity, collaboration, communication, and problem-solving skills. Bibliometric analysis using VOSviewer reveals that research trends are shifting toward the integration of technology, entrepreneurship, and sustainability issues. Furthermore, the effectiveness of PjBL-STEM implementation is influenced by the use of real-world problems, active student engagement, and interdisciplinary integration of STEM. In conclusion, STEM-integrated PjBL can serve as an effective and relevant instructional approach to improve the quality of science learning and to prepare students for the challenges of the 21st century.